(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2023)
The objective of this study was to understand the impact of storey walls on the Response of RC Framed Building. The shear wall provides huge stiffness against lateral load, making the structure less vulnerable during the Earthquake. The location of the shear wall plays a vital load defending seismic force on the building. The research method was experimental research. In this paper, the most favorable position of the shear wall was determined by creating different alternates ALT-1, ALT-2, ALT-3 and ALT-4. The results of storey drift, lateral sway and base share were computed with the base model. Finite element software ETABS was used for the linear dynamic analysis and design of 11 storey building. The results show that Lateral sway and storey drift declined with the introduction of a shear wall with a central location exhibiting the most desirable result. The implication of this study would be beneficial to the Engineering Department of OCEM, students, researchers, and scholars to know the impact of Shear Wall Location on the Response of RC Framed Buildings.